PEMBELAJARAN KONTEKSTUAL BERBANTUAN MEDIA KONKRIT UNTUK MENINGKATKAN HASIL BELAJAR IPA - Dewantari, Putu Ayu; Arkiang, Fajeri (Fakultas Psikologi Universitas Teknologi Sumbawa, 2024)
This study was intended to see an increase in the study of science if it uses the application of the context-contractual approach to assist in the concrete media in the Deaf student Class V SLB 1 Gianyar Year 2022/2023. This study is a variety of classroom action studies, which dilaksanakn through two stages or cycles, each cycle is carried out through measures, namely (1) planning (2) to carry out learning improvements (3) to observe and (4) reflectin. The subject of this study was the student of the Deafness class V SLB 1 Gianyar that totals 5 people, all male sex. The research of class action that is carried out uses test and non-stakes testing. The data obtained in kettle or analyzed by qualitative descriptive and quantitative descriptive. An examine the value of the rating on the average cycle is 74, as well as the value on the average cycle is 82. There is an increase in the average learning outcomes of the 1st cycle towards the 2nd cycle of 10.81%. Through this explanation, we can conclude the implementation of the contextual learning approach to assist in the media of the Republic of Indonesia increasing the learning outcomes of the Deafness Class V SLB 1 Gianyar Year 2022/2023.